Profil Disposisi Matematis Siswa Kemampuan Tinggi Dalam Menyelesaikan Soal Kontekstual - Suci Histiyaningsih; Dewi Sukriyah; Lailatul Mubarokah (LPPM STKIP PGRI Sidoarjo, 2020)
The purpose of this study was to describe the mathematical disposition profile of students with high mathematical abilities in solving contextual problems. This research is a qualitative descriptive study. Data collection techniques in this study were subject selection tests, mathematical disposition tests, interviews. The results of data analysis showed: subjects with high mathematical abilities in solving contextual questions showed aspects of self-confidence, flexibility, resilient teeth, and curiosity. With these results it can be drawn a statement that mathematical dispositions must always be instilled in students in every implementation of mathematics learning. In addition, the teacher's attitude in learning mathematics must be able to reflect the various characteristics of mathematical dispositions to be emulated by students.